Adherence to Good Pharmacy Practices by Community Pharmacies in Lebanon and Opportunities for Quality Improvement: It is Time to Act - Bou-Saba A; Kassak KM; Salameh P (Dove Medical Press, 2023)
Alein Bou-Saba,1,2 Kassem M Kassak,2 Pascale Salameh3- 6 1Doctoral School of Science and Technology, Lebanese University, Hadat, Lebanon; 2Faculty of Health Sciences, American University of Beirut, Beirut, Lebanon; 3School of Medicine, Lebanese American University, Byblos, Lebanon; 4Institut National de Santé Publique d'Épidémiologie Clinique et de Toxicologie-Liban (INSPECT-LB), Beirut, Lebanon; 5Department of Primary Care and Population Health, University of Nicosia Medical School, Nicosia, 2417, Cyprus; 6Faculty of Pharmacy, Lebanese University, Hadat, LebanonCorrespondence: Alein Bou-Saba, Doctoral School of Science and Technology, Lebanese University, Hadat, Lebanon, Tel +961 70980978, Email alein.bousaba@gmail.comPurpose: Good pharmacy practice is an important standard that highlight the quality of services in community pharmacies. In 2018, The Order of Pharmacists in Lebanon (OPL) published their own good pharmacy practices (GPP) guidelines. The need exists for investigational studies to assess GPP implementation status and the professional conduct of on-site staff towards these standards.Methods: Data collection was carried out between February and August 2020 using a questionnaire covering: Socio-demographic variables; Indicator A (Attitude of the Community Pharmacists); Indicator B (Services and Facilities); Indicator C (Dispensing); Indicator D (Storage). Data analysis were performed on SPSS version 25, T-Test and ANOVA were used. A significant p value of < 0.001, 95% confidence interval and variables with missing data counting less than 10% were considered.Results: A total of 211 staffers from pharmacies were enrolled in the study, each representing one community pharmacy. The mean percent of adherence to GPP standards by community pharmacies in the South of Lebanon was below the recommended threshold of 75%. Only 65.09% adhered to all tested indicators (27% to Indicator A, 56.91% to Indicator B, 68.61% to Indicator C, 66.31% to Indicator D). Higher indicators were seen among providers who were aware of OPL standards (OR = 4.021), female (OR= 2.011) and being a licensed pharmacist (OR=3.506). Cronbach alpha of the overall score was 0.615.Conclusion: Further steps shall be taken to improve the compliance to GPP standards. Steps shall include, identification of the core standards, such as dispensing, provision of adequate information, monitoring of storage conditions, and ensuring the presence of a licensed pharmacist. It is highly recommended that the OPL and the Ministry of Public Health develop a "Self-assessment tool" and an efficient training program to increase community Pharmacists' awareness status. Regular assessment shall be carried to monitor the progress overtime.Keywords: community pharmacy, good pharmacy practice, indicators, Lebanon